Applying shari'a in the West: facts, fears and the future of Islamic rules on family relations in the West - Berger, Maurits (Debates on Islam and society, 2013)
Islamic rules and norms cover a vast area of behavior and relations. The content of this edited volume will be limited to issues of family relations, with a focus on the normative behaviour and initiatives of Muslims in the West on the one hand, and the reactions thereto by Western societies and legal systems on the other. The focus will be domestic, hence excluding issues of foreign national Muslim laws and international private law. This volume intends to a) provide an overview of the current state of affairs and b) discuss aspects of future developments, studies and policies